Effect of curing temperature on the soil physical and mechanical properties on clay shale geopolymer fly ash stabilization - Hartono, Edi; Diana, Willis; Muntohar, Agus Setyo; Azhar, Muhammad; Indriani, Lia (Universitas Mercu Buana, 2025)
Clay shale is an easily degraded mudrock when exposed to weathering. The reduced strength due to degradation can be mitigated through soil stabilization. In recent years, soil stabilization using geopolymers has become one of the latest popular methods due to its economic benefits and lower carbon footprint. A widely used cementitious material for this method is fly ash-based geopolymer. The relationship between curing temperatures and the performance of clay shale stabilized with fly ash-based geopolymer has yet to be studied for the purpose of identifying a more effective stabilization method. In this study, clay shale was stabilized using geopolymer. The geopolymer was made of fly ash and an activator. Sodium hydroxide (NaOH) and sodium silicate (Na2SiO3) as activators. The activator is diluted with water to create a 12 M mixture. Before the unconfined compressive strength test, the specimens were subjected to various curing temperatures from 26oC to 60oC. The test result shows that, in general, higher curing temperatures increased the dry density from 1.66 g/cm3 to 1.84 g/cm3. Meanwhile, the unconfined compressive strength multiplies about 3.5 times. Furthermore, the moisture content decreased after the curing process from 19% to 2.5%. This led to the specimen volume experiencing decrement due to the shrinkage during the curing period. The volume reduces from 67.7 cm3 to 63.5 cm3. In general, temperature plays a significant role in enhancing the strength of clay shale stabilized using fly ash-based geopolymer.